The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.15381/anales.v73i3.862
|View full text |Cite
|
Sign up to set email alerts
|

Tamizaje de salud mental mediante el test MINI en estudiantes de Medicina

Abstract: ResumenIntroducción: Los trastornos de salud mental constituyen un problema prevalente en alumnos de educación superior, siendo los estudiantes de medicina una población especialmente vulnerable. Objetivos: Determinar la frecuencia de trastornos de salud mental en los alumnos de una escuela de medicina. Diseño: Estudio descriptivo, transversal. Institución: Escuela de Medicina, Universidad Católica Santo Toribio de Mogrovejo, Chiclayo, Lambayeque, Perú. Participantes: Alumnos de una escuela de medicina. Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
3
1
3
Order By: Relevance
“…In our study, we found a higher prevalence of suicide risk than the reported in previous national studies . This shows a worrying trend and might be related to the increase in the number of medical students and medical schools in our country .…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, we found a higher prevalence of suicide risk than the reported in previous national studies . This shows a worrying trend and might be related to the increase in the number of medical students and medical schools in our country .…”
Section: Discussioncontrasting
confidence: 57%
“…In the case of Peru, two studies that relate dropouts and mental health-related issues within a medicine student population have been conducted. The first one, that analyzed dropout rates in 2010, concluded that 22% of the students had at least one mental health-related problem ( León-Jimenez et al., 2012 ); while the second one, that examined these rates between 2006 and 2014, found that only 5.7% withdrew due to mental health-related reasons ( Necochea Ocaña et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Probablemente esto se deba a sesgo de información, ya que en un estudio en el 2010 en la Escuela de Medicina de esta Universidad, se encontró que 22% de los alumnos tenían al menos un problema de salud mental, y 6,9% y 5,6%, tuvieron riesgo suicida y trastorno depresivo, respectivamente (17).…”
Section: Discussionunclassified